Synthesis, Characterization and Antimicrobial Activity of New 4-aminoantipyrine Derivatives Using Ultrasonic Mediation (Baghdad Science Journal, 2024)
A straightforward, one-pot, three-component reaction between substituted aromatic aldehydes, 2-naphthol and 4- aminoantipyrine have been used to synthesis a series of new 4-(((2-hydroxynaphthalen-1-yl) (phenyl) methylene) amino)-1,5-dimethyl-2-phenyl-1,2-dihydro-3H-pyrazol-3-one derivatives (A1- A5). This reaction was carried out with zirconyl chloride (ZrOCl2.8H2O) as an efficient catalyst under the condition of ultrasound irradiation. The fact that these derivatives have the potential to act as building blocks in the production of new compounds makes them very essential 4-(1-phenyl-1H-naphtho[1,2-e] [1,3] oxazin-2(3H)-yl)- 1,5-dimethyl-2-phenyl-1,2-dihydro-3H-pyrazol-3-one derivatives (A6, A7 and A8). Likewise, the MCRs that resulted in the formation of hetero cyclic compound (1,3-naphthoxazine) and included 4-aminoantipyrine, formaldehyde, and 2-naphthol in a mole ratio of 1:2:1 have been employed to generate 4- (1H-naphtho [1,2-e] [1,3] oxazin-2(3H)-yl)-2-phenyl-1, 5-dimethyl-1,2-dihydro-3H-pyrazol-3-one (A9). This reaction begins with the introduction of ZrOCl2-K2CO3 catalyst system and proceeds through condensation and cyclization. All produced compounds were analyzed through IR, 1H NMR, and 13C NMR spectra data to illustrate each of these distinct structures. Using the broth microdilution and disc diffusion method, the antibacterial and anti-fungal activities of the compounds were evaluated against Gram-positive, Gram-negative, in comparison to conventional medicines (Ampicillin, Ciprofloxacin and Amoxycilline). The synthesized compounds had a wide range of action, with MIC values of 200, 600 and 1000 µg/ml against the investigated bacteria, as determined by microbiological analysis.